TAX INFORMATION AS IMPROPER EVIDENCE WHEN THE COURT RESOLVES A TAX DISPUTE - Ugolkov, Evgen (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to find ways to solve the problem of using tax information from the databases of the DPS information systems by the tax authority without checking the primary documentation on the basis of which such information was entered into the relevant databases. Research methods: a set of methods used in modern legal science, in particular, special research methods (comparative-legal, logical-legal, formal-legal) and general scientific (dialectical, systemic-functional, analogies) research methods were used. Results: when forming conclusions based on the results of a tax audit, the tax authority cannot refer to the tax information available in the databases of the DPS information systems as unconditional evidence without checking the primary documentation on the basis of which such information was entered into the databases. Discussion: premature application by the tax authority of tax information from the databases of the DPS information systems, without proper verification of primary documents, leads to negative consequences for taxpayers, since such information is the basis for conclusions based on the results of a tax audit.